Efficient and Scalable Large-Area Organic Solar Cells by Asymmetric Nonfullerene Acceptors Based on 9H-Indeno[1,2-b]pyrazine-2,3,8-Tricarbonitrile - Gopikrishna, Peddaboodi; Rhee, JinHyeong; Yoon, Seongwon; Um, DuHyeon; Jin, Hyunjung; Jun, Yongseok; Choi, Huijeong; Son, Hae Jung; Kim, BongSoo (John Wiley & Sons Ltd., 2023)
It remains challenging to fabricate efficient, scalable large-area organic solar cells (OSCs) owing to the unfavorable morphology of photoactive blend films. To address this challenge, two asymmetric nonfullerene acceptors (NFAs) IPC1CN-BBO-IC2F and IPC1CN-BBO-IC2Cl are synthesized, where 12,13-bis(2-butyloctyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]thiadiazolo[3,4-e]thieno[2 & PRIME;",3 & PRIME;":4 & PRIME;,5 & PRIME;]thieno[2 & PRIME;,3 & PRIME;:4,5]pyrrolo[3,2-g]thieno[2 & PRIME;,3 & PRIME;:4,5]thieno-[3,2-b]indole (BBO) is the molecular core, and two types of end groups are appended to its ends, namely the 9H-indeno[1,2-b]pyrazine-2,3,8-tricarbonitrile (IPC1CN) end group and one of 2-(5,6-dihalo-3-oxo-2,3-dihydro-1H-inden-1-ylidene)malononitrile end groups (IC2F or IC2Cl). These NFAs facilitate effective tuning of light absorption and energy levels, offer high carrier mobilities, and allow for the formation of appropriate morphologies. Note that these benefits apply even to large-area devices, unlike typical Y6-based NFAs. In addition, a random copolymer PM6-PBDBT(55) is synthesized and its energy levels are optimally matched with those of the asymmetric NFAs. The blade-coated 1 cm(2)-area OSCs based on PM6-PBDBT(55):IPC1CN-BBO-IC2Cl exhibit a PCE of 14.12%, which is higher than that of PM6-PBDBT(55)-IPC1CN-BBO-IC2F-based OSCs. More importantly, the PM6-PBDBT(55):IPC1CN-BBO-IC2Cl-based large-area (58.50 cm(2)) modules yield an impressive PCE of 11.28% with a small cell-to-module loss in fill factor. These results suggest that a combination of the asymmetric molecular design using the IPC1CN group and the terpolymer strategy will pave a new path for fabricating highly efficient and scalable large-area OSCs.